2018
DOI: 10.1016/j.bpsc.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Rostral Anterior Cingulate Cortex Morphology Predicts Treatment Response to Internet-Based Cognitive Behavioral Therapy for Depression

Abstract: Background Rostral and subgenual anterior cingulate cortex (rACC and sgACC) activity and, to a lesser extent, volume have been shown to predict depressive symptom improvement across different antidepressant treatments. This study extends prior work by examining whether rACC and/or sgACC morphology predicts treatment response to internet-based cognitive behavioral therapy (iCBT) for major depressive disorder (MDD). This is the first study to examine neural predictors of response to iCBT. Methods Hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 60 publications
2
22
0
1
Order By: Relevance
“…One study showed that the long‐term outcome of ICBT for social anxiety disorder could be predicted by blood oxygen level‐dependent (BOLD) responses to self‐referential criticism in the fear‐expressing dorsal anterior cingulate cortex and amygdala regions at pre‐treatment, analyzed using a support vector machine learning approach. Another study found that larger pre‐treatment right rostral anterior cingulate cortex volume was a significant predictor of greater depressive symptom improvement on ICBT, even after controlling for demographic and clinical variables previously linked to treatment response.…”
Section: Mechanisms Of Change and Predictors Of Outcomementioning
confidence: 98%
“…One study showed that the long‐term outcome of ICBT for social anxiety disorder could be predicted by blood oxygen level‐dependent (BOLD) responses to self‐referential criticism in the fear‐expressing dorsal anterior cingulate cortex and amygdala regions at pre‐treatment, analyzed using a support vector machine learning approach. Another study found that larger pre‐treatment right rostral anterior cingulate cortex volume was a significant predictor of greater depressive symptom improvement on ICBT, even after controlling for demographic and clinical variables previously linked to treatment response.…”
Section: Mechanisms Of Change and Predictors Of Outcomementioning
confidence: 98%
“…The results showed that offspring of parents with BD had lower functional connectivity between the right ventral striatumleft caudal anterior cingulate in response to loss; and higher functional connectivity between the right pars orbitalis-left and right orbitofrontal cortex in response to reward, indicating potential neural markers for the risk of BD. 255 Despite the impressive advances in technology and interesting neuroimaging findings associated with a psychiatric diagnosis, 247 as well as the response to treatment and risk identification, 255,256 there is still no direct clinical application of brain imaging at this moment in psychiatry.…”
Section: Neuroimaging Findings In Bipolar Disordermentioning
confidence: 99%
“…Despite the impressive advances in technology and interesting neuroimaging findings associated with a psychiatric diagnosis, 247 as well as the response to treatment and risk identification, 255 , 256 there is still no direct clinical application of brain imaging at this moment in psychiatry.…”
Section: Neuroimaging Findings In Bipolar Disordermentioning
confidence: 99%
“…The rostral anterior cingulate cortex (rACC), located at the genu of the corpus callosum, may also have features predictive of treatment outcome in depression. Early studies of regional glucose metabolism using positron emission tomography (PET) identified greater rACC glucose metabolism as a predictor of response to pharmacotherapy in depression [6,14,15], and rACC volume predicted response to an internet-based CBT intervention, while SCC volume did not [16]. A recent longitudinal study found that restingstate functional connectivity (rsFC) of the rACC with the salience network predicted reductions in depressive symptoms in general, irrespective of treatment type [17].…”
Section: Introductionmentioning
confidence: 99%